Management Control, From Traditional Practice To The Use Of Artificial Intelligence - Boukssessa, Souhila Kheira (جامعة الوادي University of Eloued, 2025)
In the context of digital transformation, artificial intelligence now holds a central place in the strategy of organizations. It is involved in all functions of the enterprise, and management control does not seem to be spared. Research is beginning to question the evolution of the role of management control in this new environment. Management control is a system based on the collection and analysis of information with the aim of providing leaders with information to assist them in their strategic decision-making to achieve the company's desired objectives. The integration of artificial intelligence into this system offers significant benefits such as automating repetitive tasks, optimizing decision-making processes, and quickly identifying trends. The goal of this research is to study the growing influence of artificial intelligence on the management control function and the role of the controller. It examines how emerging technologies such as big data and predictive analysis transform traditional management control processes.
مقال
Keywords: Management control; Artificial Intelligence; Big data; Business partner; decision-making